What would be the best way to solve the following the following system of equations? $$x^2+y^2+6y+5=0$$ $$x^2+y^2-2x-8=0$$

This is how I did it, but I am hoping there is a simpler way.

Subtracting the two equations, I get $$6y+2x+13=0$$which simplifies to $$x=-3y-\dfrac{13}2$$I substitute it into the first equation where I get $$9y^2+39y+\dfrac{169}4+y^2+6y+5=0$$ and solving for $y$ I get $$y=-\dfrac{45\pm\sqrt{1552.5}}{20}$$which simplifies to $$y=-\dfrac{9\pm{\sqrt{62.1}}}{4}$$ Plugging this back into the equation at the beginning of this highlighted section I get $$\dfrac{-53\pm{3\sqrt{62.1}}}{2}=-2x$$or $$x=\dfrac{53\pm{3\sqrt{62.1}}}{4}$$ So my final answer is $$\big(\dfrac{53\pm{3\sqrt{62.1}}}{4},-\dfrac{9\pm{\sqrt{62.1}}}{4})$$


After the substitution, we have

$$10y^2 + 45 y + \dfrac{189}{4} \implies y_{1, 2} = -\dfrac{9}{4} \pm \dfrac{3~ \sqrt{\dfrac{3}{5}}}{4}$$

This leads to

$$ x_{1, 2} = \dfrac{1}{4} \mp \dfrac{9~ \sqrt{\dfrac{3}{5}}}{4}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.